Income Distribution Effects of EU Rural Development Policies: The Case of Farm Investment Support - Pavel Ciaian; Tomáš Ratinger (Economics and Econometrics Research Institute (EERI), 2009)
This paper analyses income distribution effects of investment support granted under the EU Rural Development Policies (RDP). In the short-run and with perfect credit markets, the size of gains for farms depends on the extent to which investment additionality is enforced. If additionality is not enforced, farms gain an important share of the total support but do not have incentive to increase capital use. If additionality is enforced, gains for farms are lower and farms can even lose. With imperfect rural credit markets, farms would most likely prefer to increase capital use even without enforcement of investment additionality and total welfare increases. In the long-run farm benefits from this investment may be enhanced because of the multiplier effect. Introducing minimum thresholds as eligibility criteria may deter small farms from uptaking the investment support even if investment additionally is not enforced. Benefits from investment support are shared with capital suppliers. Gains of capital suppliers depend on the size of the capital supply elasticity and are conditional on the EU support to increase farm capital demand.
Keywords: Q12; Q18; 330; Rural development policies; policy rents; policy modelling; farm investment